On one class of topological *-algebras with standard identities - Tishchenko, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Let A be a unital semisimple topological nuclear *-algebra over C and let Z be its center. Then A is topologically isomorphic to M n (Z) if and only if A satisfies the standart identity and the maximality condition.